The Asian disease: Plausible diagnoses, possible remedies. Regulation of cross-border interbank lending and derivatives trade - Martin Mayer (Levy Economics Institute of Bard College, 1998)
Asia presents a cumulation of apparently rational decisions that produced disastrous results - a textbook illustration of financial instability developing from the economics of euphoria. A combination of factors produced the crisis as enormous capital inflows were drawn to the Asian miracle-pegged exchange rates with fluctuating interest rates, integrated economies, moral hazard created by central banks, and short-term lending and derivatives trade without sufficient evaluation of risk and credit analysis of borrowers. The Asian tragedy demonstrates the need for improved regulation of cross-border interbank lending, improved accounting for both borrowers and lenders, and separation of the close links between governments and their banking sector.
Keywords: 330